The Effect of Benzyl Amino Purine (BAP) on Indirect Organogenesis of the Titan Arum (Amorphophallus titanum (Becc.)) - Putri Salsa Afifah; Yusniwati Yusniwati; Aprizal Zainal; Ryan Budi Setiawan (Agrosains : Jurnal Penelitian Agronomi, 2025)
The titan arum (Amorphophallus titanum (Becc.)), an endangered and endemic flora from the island of Sumatra, faces a significant risk of extinction. Conservation efforts for the titan arum were undertaken, including in vitro conservation through tissue culture. The study aimed to determine the optimal concentration of the growth regulator Benzyl Amino Purine (BAP) for inducing shoot formation in titan arum and to observe cellular changes during the shoot stage through histological test. This research was conducted from November 2023 to March 2024 at the Tissue Culture Laboratory, Andalas University. The experiment was arranged in a Completely Randomized Design (CRD) with five treatment levels: 2, 3, 4, 5, and 6 ppm.  Data analysis was performed using an F-test at a 5% significance level. If the F-test showed significant differences, further testing was carried out using Duncan's Multiple Range Test (DMRT) at a 5% significance level. Meanwhile, data on explant rooting percentage and root count were presented as means and standard deviations. Results indicated that various concentrations of BAP could induce shoots formation of Amorphophallus titanum Becc., with the percentage of explants forming shoots reaching 80–95%.  The concentration of 5.0 ppm BAP was the most effective, yielding the highest average number of shoots at 7.80. Histological test revealed cell enlargement at the shoot tips. This research is pivotal for the conservation of titan arum and promotes further studies in in vitro culture techniques.